The Drosophila gene asteroid encodes a novel protein and displays dosage-sensitive interactions with Star and Egfr. - Kotarski, M.A.; Leonard, D.A.; Bennett, S.A.; Bishop, C.P.; Wahn, S.D.; Sedore, S.A.; Shrader, M. (Genome, 1998)
The asteroid gene of Drosophila was found to lie within 189 bp of Star. Asteroid cDNA clones were isolated and sequenced and a single putative open reading frame was identified that encodes a novel protein of 815 amino acids with a calculated molecular mass of 93 kilodaltons. Using cDNA probes, asteroid transcripts were localized to the proliferative tissues of embryos and to the mitotically active tissue anterior to the morphogenetic furrow in eye imaginal discs. Ribonuclease protection assays identified a mutation of asteroid that acts as a dominant enhancer of Star mutations and also enhances the Ellipse mutation, EgfrE1. Based on these data, a model for asteroid gene function in EGF receptor signaling is presented.